Comparison of the Effect of Dipeptidyl Peptidase-4 Inhibitors Sitagliptin and Vildagliptin on Intestinal Motility of Rabbit Ileum and Rat Gastric Fundus Tissue (Journal of Fatima Jinnah Medical University, 2024)
ABSTRACTBackground: Diabetes mellitus is a pervasive metabolic disorder. Its prevalence is very high all over the world. Long-standing disease may result in many complications including diabetic gastroparesis. Research to evaluate the impact of antidiabetic drugs on intestinal motility is an important field of researchMaterials and methods: This study was performed in CMH Lahore Medical College and FJMU, Lahore, on isolated tissues obtained from adult healthy rabbits and rats over 18 months. Animals were divided into four groups of each species; each group comprised twenty animals. Strips of rabbit ileum and rat gastric fundus tissues were allowed to stand in physiological salt solution in an organ bath with transducers attached to the Powerlab. Increasing concentrations of Sitagliptin and Vildagliptin were administered and a change in intestinal motility was recorded by powerlab (AD instruments) as a change in the force of contraction(g). Then increasing concentrations of sitagliptin and vildagliptin,were administered in the presence of ondansetron. Unpaired t-test was used to compare the difference between the two groups of drugs A p-value of less than 0.05 was considered significant. Results: There was a dose-dependent inhibitory effect of sitagliptin and vildagliptin on intestinal motility.Sitagliptin has an inhibitory effect when administered alone and change the force of contraction from 19.86±1.71 to 14.00±1.5 on rabbit ileum and from 9.008±1.3 to 6.4±1.18 on rat gastric fundus tissue. Sitagliptin in the presence of ondansetron has dual effect at low concentrations it has inhibitory effect and at high concentration it has stimulatory effect. Sitagliptin has more significant inhibitory effects on the force of contraction as compared to vildagliptin (p-value < 0.001). Conclusion: The Present study confirms the inhibitory effect of sitagliptin and vildagliptin on the gastrointestinal motility.
Keywords: Sitagliptin; Vildagliptin; Gastroparesis; Isolated tissue